Death's bright day - Drake, David, 1945- (Drake, David, 1945- RCN series., 2017)
"Dispatched by high-ranking officials to a distant but critical star system, naval captain Daniel Leary and cybrarian spy Adele Murphy are challenged to prevent a war between the Republic of Cinnabar and their rival, the Alliance of Free Stars"--